Actual challenges in materials science and processing technologies : special topic volume with peer reviewed papers only - Pivnyak, Gennadiy (Trans Tech Publications Ltd, 2020)
Special topic volume with invited peer reviewed papers only.
Keywords: Materials science -- Technological innovations.; elektronické knihy; electronic books